Ecoliteracy of Junior High School Students through Phenomenon Based Learning on the Interaction of Living Things with the Environment - Iman Kadarisman; Indarini Dwi Pursitasari; Dadang Jaenudin (Jurnal Penelitian Pendidikan IPA, 2023)
Ecoliteracy and Education for Sustainable Development (ESD) have received attention in achieving the Sustainable Development Goals (SDGs). Students' understanding of the environment and sustainability awareness needs to be instilled through the Phenomenon Based Learning model. This study aims to improve students' ecoliteracy through Phenomenon Based Learning on the material of the interaction of living things and the environment. The research used quasy experiment method with research design Only Pretest-Posttest Control Group Design. The research subjects were junior high school students in grade VII.Â  Data collection techniques used tests, questionnaires, interviews and observations. Data analysis was done descriptively, N-gain calculation, and Mann Whitney test. The results showed that the average N-Gain of ecoliteracy for affective, psychomotor, spiritual, and cognitive aspects were 75.02%; 45.84%; 79.73%; and 73.31%, respectively. Mann Whitney test results showed significant differences in student ecoliteracy in experimental and control classes. Thus, it can be concluded that the implementation of learning using the PhenoBL model can improve student ecoliteracy with high categories for affective, spiritual, and cognitive aspects, while the increase in student ecoliteracy in the psychomotor aspect is classified as moderate.